REFERENCE POINT AND EXPLOITATION STATUS OF MUD SPINY LOBSTER (Panulirus polyphagus Herbst, 1793) IN SEBATIK WATERS, INDONESIA - Tirtadanu Tirtadanu; Umi Chodrijah; Karsono Wagiyo (Research Center for Fisheries, 2021)
The important information that was needed for determining the sustainable management of mud spiny lobster (Panulirus polyphagus Herbst, 1793) in Sebatik Waters were the exploitation status and the reference point. The aims of this research was to study the reference point and the exploitation status of P. polyphagus. This research was conducted from March 2016 to December 2018 and the total samples of 1.261 female lobsters had been collected monthly from the traditional gillnet fishers in Sebatik. Reference point was determined from the Beverton and Holt yield per recruit and the exploitation status was estimated from the length based spawning potential ratio (LB-SPR). The results showed that a lot of P. polyphagus catched by the gillnets were still immature. The annual spawning potential ratios from 2016 to 2018 were still lower than the reference point of 24% that showed the overexploited status of P. polyphagus in Sebatik Waters. The minimum legal size of 87 mmCL or the minimum weights of 500 grams and not increasing the quota vessels following by the monitoring study of its stock for the next several years were some recommendations for the sustainable P. polyphagus management in Sebatik Waters.